The Implementation of Islamic-Based Interprofessional Collaboration on the Quality of Life of Older Adults - Fitriani, Aidah; Sutria, Eny; Azizah, Nur (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2025)
Older adults frequently encounter fragmented healthcare services that predominantly focus on medical aspects. One contributing factor is the limited implementation of interprofessional collaboration (IPC), both in health and non-health sectors, due to insufficient understanding, facilities, and infrastructure. These limitations may negatively impact the quality of life of older adults. Therefore, this study aimed to examine the effect of implementing Islamic-based Interprofessional Collaboration (IPC) on the quality of life of older adults at Sentra Gau Mabaji Gowa. This research employed a quasi-experimental design with a quantitative approach and was conducted from May to July 2024. The sample consisted of older adults at Sentra Gau Mabaji Gowa. The World Health Organization Quality of Life for Older Adults (WHOQOL-Old) instrument was used, and data were analyzed using the Paired t-test. The results indicated a significant effect of the Islamic-based IPC implementation on the quality of life of older adults, with a p-value of 0.023. The better the implementation of IPC, the better the quality of life of the elderly.